School-based Management Practices Among Public Schools in Region I: Basis for Technical Assistance Plan - Ritchie G. Macalanda (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study focused on school-based management practices among public school in Region I, this school year 2021-2022. The respondents in this study are the school heads in both public elementary and secondary schools. Results showed that most of the school heads are at middle adulthood age, female, married, full-pledged principal, mostly Principal IV, had been serving for long years as principal, mostly doctorate degree holders, have adequate relevant trainings, financially stable and has outstanding performance. Most of the schools are in the rural area and medium in size. Schools have average MOOE allocation. In terms of performance indicators, the schools should look into the dropout rate and completion rate. The implementation of the SBM in terms of leadership and governance, curriculum and instruction, accountability and continuous improvement is recorded to be at maturing level (Level 2). On the other hand, management of resources is at level 3 advanced. There is a significant relationship between the SBM level of practice along leadership and governance, curriculum and learning, accountability and continuous improvement, and management of resources and the profile variables of the school principals. Indicators on SBM in the four areas showed insignificant relationship.